Doping in recreational sport as a risk management strategy - Werner Pitsch (Journal of Risk and Financial Management, 2022)
Knowledge about the prevalence of doping in recreational sports is still limited and fragmented. The same holds true for explanations of doping prevalence rates among different groups. One of the few theoretical models that exists uses the concept of consumer capital based on Stigler and Becker's theory of rational addiction. Building on the largest study on doping in recreational sports that has ever been conducted in Europe, the FAIR+ survey, hypotheses on the differences in doping prevalence rates, by the level of participation in competitions and by the relative time spent participating in the sport are, developed. Statistical tests support the model while also drawing attention to the limitations of this theoretical explanation.
Keywords: 650; consumer capital; indirect questioning techniques; mass sport; performance enhancing drugs (PED); Randomized Response Technique (RRT); rational addiction theory